An improved analytical thermal rating method for cables installed in short-conduits. (December 2020) - Liu, Gang; Xu, Zhifeng; Ma, Hui; Hao, Yanpeng; Wang, Pengyu; Wu, Wenbo; Xie, Yue; Guo, Deming
Highlights: A simplified model for the real-time thermal rating of short-conduit cable. An iterative solution method for the simplified model is implemented. The accuracy of the simplified model is verified by the finite element method. Performance of the simplified model comparing with the IEC method is presented. Abstract: In urban underground environment, a short-conduit is commonly used to provide mechanical protection for the cable. The cable section buried in the short-conduit may experience excessive thermal stresses. However, the thermal rating for the cable in the short-conduit is not specialized in the IEC 60287. It has not been sufficiently addressed in the literature either. This paper proposes a quasi-three-dimensional thermal model for the cable installed in the short-conduit. A simplified model for efficiently and effectively solving the proposed model is then developed. Based on the simplified thermal model, an improved method for assessing the real-time ampacity of the cable installed in the short-conduit is implemented. The performance of the improved method with respect to the IEC method on thermal rating for the cable installed in the short-conduit is verified by the Finite Element Analysis (FEA). The results show that the improved method outperforms the IEC method when the conduit length is less than five meters. The method is useful in real-time thermal rating of the short-conduit cables and paves a way to increase the utilization of cables installed in short-conduits while still ensuring their reliability.